The Relationship of Icon, Indices and Symbols in The Comic Al-Sindibād Al- Baḥrī by ‘Abd Al-Jabbār Nāṣir Semiotic Review of Charles Sanders Pierce: Relasi Ikon, Indeks Dan Simbol Dalam Komik Al-Sindibād Al-Baḥrī Karya ‘Abd Al-Jabbār Nāṣir (Tinjauan Semiotika Charles Sanders Peirce) - Izzatul Jannah; Zulkhairi; Chairunnisa Ahsana AS (Pusaka Cendekia Indonesia Foundation, 2025)
The aim of this research is to understand the semiotic meaning contained in the triangle symbol in the comic story